Support to the Development of Legal and Institutional Frameworks on Access to Genetic Resources and related Benefit Sharing and Traditional Knowledge in line with the CBD and its Nagoya Protocol in Venezuela - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
The "Support for the Development of Legal and Institutional Frameworks on Access to Genetic Resources and Benefit Sharing in Venezuela" project aims to strengthen local capacities for implementing an access and benefit-sharing (ABS) regime in line with the Nagoya Protocol and the Convention on Biological Diversity (CBD). Among its key objectives, the project will develop a coordinated inter-institutional framework, including legal and administrative strategies to regulate access and ensure fair benefit-sharing. It will also focus on training key stakeholders (government, indigenous communities, the private sector, and academia) to effectively manage genetic resources. Additionally, the project will promote regional cooperation with Latin American and Caribbean countries to facilitate experience-sharing in ABS implementation. These actions are expected to contribute to biodiversity conservation and sustainable development in Venezuela.